Three Years After Transplants in Human Mandibles, Histological and In‐Line Holotomography Revealed That Stem Cells Regenerated a Compact Rather Than a Spongy Bone: Biological and Clinical Implications. (15th March 2013) - Giuliani, Alessandra; Manescu, Adrian; Langer, Max; Rustichelli, Franco; Desiderio, Vincenzo; Paino, Francesca; De Rosa, Alfredo; Laino, Luigi; d'Aquino, Riccardo; Tirino, Virginia; Papaccio, Gianpaolo
Abstract : The stability and quality of regenerated bone and vessel network was assessed 3 years after grafting intervention, with conventional procedures and in‐line holotomography. The regenerated tissue from the graft sites was found to be composed of a fully compact bone with a higher matrix density than control human alveolar spongy bone from the same patient. Although the bone regenerated at the graft sites is not of the proper type found in the mandible, it creates steadier mandibles, may well increase implant stability, and, additionally, may improve resistance to mechanical, physical, chemical, and pharmacological agents. Abstract : Mesenchymal stem cells deriving from dental pulp differentiate into osteoblasts capable of producing bone. In previous studies, we extensively demonstrated that, when seeded on collagen I scaffolds, these cells can be conveniently used for the repair of human mandible defects. Here, we assess the stability and quality of the regenerated bone and vessel network 3 years after the grafting intervention, with conventional procedures and in‐line holotomography, an advanced phase‐imaging method using synchrotron radiation that offers improved sensitivity toward low‐absorbing structures. We found that the regenerated tissue from the graft sites was composed of a fully compact bone with a higher matrix density than control human alveolar spongy bone from the same patient. Thus, the regenerated bone, being entirely compact, is completely different from normal alveolar bone. Although the bone regenerated at the graft sites is not of the proper type found in the mandible, it does seem to have a positive clinical impact. In fact, it creates steadier mandibles, may well increase implant stability, and, additionally, may improve resistance to mechanical, physical, chemical, and pharmacological agents.